DEEPTHELING AND DEVELOPMENT OF FIQH MATERIALS CHAPTER ZAKAT CLASS X AT ISLAMIC SENIOR HIGH SCHOOL - Mariani; Mahyuddin Barni (DHABIT : Jurnal Pendidikan Islam, 2024)
In supporting educational success, textbooks are needed as a tool to guide the learning process. Where, textbook contains materials are used as learning resources. Thus as a teacher must be able to master the teaching materials and develop them. This article aims to analyze the appropriateness of Zakat material in Class X at Islamic Senior High School Fiqh Curriculum 2013 Revision 2020 which is seen from psychological, cognitive, philosophical, sociological, and evaluation aspects. This study is conducted with literature review. Based on the results of the analysis, the in-depth study of Zakat material is not fully appropriate and still needs to be developed. When viewed from psychological aspect, the material is appropriate for the age of teenagers in Class the aspect, form the philosophical and sociological aspects are quite appropriate and form evaluation aspect is appropriate too however the author developed questions those were more appropriate to current developments.